2010
DOI: 10.2164/jandrol.109.009977
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Microsurgical Inguinal Varicocelectomy on Testicular Blood Flow

Abstract: We aimed to investigate the long-term effect of microsurgical inguinal varicocelectomy on testicular blood flow using color Doppler sonography (CDS) in this observational study. A total of 30 patients clinically diagnosed with left varicocele who underwent a microsurgical inguinal varicocelectomy were examined 3 times with CDS for testicular blood flow parameters, first before, then 3 months after, and finally 6 months after the operation. CDS values of testicular blood flow (peak systolic velocity, end diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 21 publications
6
42
1
Order By: Relevance
“…The authors criticized themselves, as very early postoperative evaluation may not provide accurate information about testicular hemodynamics. Similar to Tarhan et al [12], we also think that late assessment of these parameters would provide more information about the microhemodynamics of the testes and the success of the operation because it may take several months for the edema and inflammation in the operative field to recover. We think that a greater number of significant correlations between the pre-operative and second postoperative values proves this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…The authors criticized themselves, as very early postoperative evaluation may not provide accurate information about testicular hemodynamics. Similar to Tarhan et al [12], we also think that late assessment of these parameters would provide more information about the microhemodynamics of the testes and the success of the operation because it may take several months for the edema and inflammation in the operative field to recover. We think that a greater number of significant correlations between the pre-operative and second postoperative values proves this hypothesis.…”
Section: Discussionsupporting
confidence: 56%
“…The PSV and EDV were increased in the left TA, and the RI and PI of the left CA and ITA were decreased, but the authors did not observe any change in these parameters in the right arteries. They also found a significant correlation between the semen analysis and the PSV, RI, and PI of the left CA [12]. With a significant correlation between improved testicular hemodynamics and semen parameters, the authors suggested that testicular blood flow parameters could be used in the postoperative follow-up of patients with varicocele.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Studies involving RI measurements in patients with abnormal semen analysis have shown increased RI values compared to the threshold value of 0.60, and color-Doppler studies performed in azoospermic patients have allegedly shown that the quality and quantity of the ejaculate depend on the degree of blood circulation in the testicles. Reduced arterial perfusion was observed in patients with varicocele and impaired spermatogenesis, probably as a result of a metabolic deficiency affecting the microcirculation [37].…”
Section: Varicocele In Adult Malesmentioning
confidence: 95%